A Model of Academic, Personality, and Emotion-Related Predictors of University Academic Performance - Sanchez-Ruiz, Maria-Jose; El Khoury, Jamil (Frontiers in Psychology, 2019)
This paper investigates the relationships between personality (i.e., trait Emotional Intelligence-trait EI- and the Big Five) and academic performance (AP). Academic motivation, procrastination and major satisfaction were also studied. The sample consisted of 201 Lebanese undergraduates. The model represented a good fit. There was a negative direct effect of procrastination on AP and positive direct effects of major satisfaction and absorption on AP. Trait EI showed a negative direct effect on procrastination and a positive direct effect on major satisfaction, which, in turn, significantly predicted AP. Also, conscientiousness indirectly predicted AP, via procrastination, major satisfaction, and absorption. Findings point at individual differences contributing to AP and can be helpful to students, educators and counsellors in higher education.